Peer support groups for parent-carers of children with attention deficit hyperactivity disorder: the importance of solidarity as care. Issue 9 (26th November 2019) - Klein, Orly; Walker, Carl; Aumann, Kim; Anjos, Karin; Terry, Jenny
Abstract: Parent-carers of children with complex needs often lead lives impacted by challenging constellations of disadvantage and can become enmeshed in complex and contradictory tapestries of care structures and relations. Against a backdrop of financial austerity and under-resourced or exclusionary service practices, peer support groups may become increasingly important and confer valuable benefits not available elsewhere. This article focuses on one such group developed for parent-carers of children diagnosed with attention deficit hyperactivity disorder, and reports on semi-structured interviews with 13 parent-carers. Drawing upon Pols' empirical ethics of care, we nuance and detail the care that emerged in these settings, highlighting the material and relational practices that developed. We conclude that peer support groups can offer new and vital possibilities, re-situating participants from individualised positions of burden, isolation and social exclusion to confident, positive, active connectedness, by means of an affective and effective relational process we call 'solidarity-as-care'.